2006
DOI: 10.1007/11795131_78
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Support Vector Machine Model for Intrusion Detection

Abstract: Abstract. Design and implementation of intrusion detection systems remain an important research issue in order to maintain proper network security. Support Vector Machines (SVM) as a classical pattern recognition tool have been widely used for intrusion detection. However, conventional SVM methods do not concern different characteristics of features in building an intrusion detection system. We propose an enhanced SVM model with a weighted kernel function based on features of the training data for intrusion de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The final training/test phase is concerned with the development and evaluation on a test set of the final RF model that is created based on the optimal hyper-parameters set found so far from the model selection phase [26]. After getting the parameters of RF with 41 features and selected 25 features as described in section 5 and 6 respectively, we build the model by using the whole train dataset (KDD99Train+) for the RF classifier and finally, we test the model by using the test dataset (KDD99Test+).…”
Section: Resultsmentioning
confidence: 99%
“…The final training/test phase is concerned with the development and evaluation on a test set of the final RF model that is created based on the optimal hyper-parameters set found so far from the model selection phase [26]. After getting the parameters of RF with 41 features and selected 25 features as described in section 5 and 6 respectively, we build the model by using the whole train dataset (KDD99Train+) for the RF classifier and finally, we test the model by using the test dataset (KDD99Test+).…”
Section: Resultsmentioning
confidence: 99%
“…This is because FIN can self-adapt (optimize) its training parameters (window size, DTT level, dimension of FIN) utilizing such features as index of inseparability and fast training time. At the same time, successful applications of SVM (like those reported in [43] and [44]) are based essentially on a choice and/or enhancement of a suitable kernel function. Moreover, SVM usually needs a row of preliminary tricks with rough data.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, SVM usually needs a row of preliminary tricks with rough data. For example, an enhanced SVM for intrusion detection in [44] needs at least four steps to adopt KDD data [39]: (1) consider only binary classification, (2) filter the ''redundant'' intrusion records, (3) perform feature ranking and (4) delete the ''unimportant'' features. Note that FIN is free of similar steps and is applied directly to the same KDD data [45].…”
Section: Discussionmentioning
confidence: 99%
“…From the study of measuring the performance of detecting intrusions among NB, rTree, and rForest, they identified that rForest is superior to others with maintaining low false alarm rate. Interestingly, many researchers used SVM to conduct intrusion detection analysis [43][44][45][46][47] because it is good for classifying data by finding a hyperplane that maximizes the margin among all intrusion classes. It simply classifies the input data by a set of support vectors representing data patterns.…”
Section: Classification Algorithmsmentioning
confidence: 99%